Drug rash with eosinophilia and systemic symptoms, uncommon and commonly missed - Das, Dona; Ragav, Dinesh E.; Begum, A. Nasreen (International Journal of Advances in Medicine, 2019)
Drug Rash with eosinophilia and systemic symptoms, also called DRESS syndrome, is a rare form of drug induced hypersensitivity reaction that presents with skin eruptions, blood count abnormalities (eosinophilia) and internal organ involvement (lung, kidney, liver), making it life threatening at a rapid pace. The most commonly affected organ is liver, mimicking condition similar to acute hepatitis.